Gender Differences in Implicit Processing of Sexual Stimuli - Marieke Dewitte (2015)
The present studies investigated whether men and women differ in cognitive–motivational processing of sexual stimuli in order to better understand the commonly observed gender differences in sexual outcome variables. Because these processes often operate without conscious control, we focused specifically on automatic stimulus processing. Using a series of implicit tasks, we measured inhibition, attentional orientation, appraisal and approach–avoidance motivation regarding sexually explicit stimuli in male and female students. Results showed that men were more strongly motivated to approach sexual stimuli than women and were better able to inhibit sexual information as to prevent activation of the sexual response. With regard to attentional orientation, men were more easily drawn by sexual cues than women, yet only when the cues were presented long enough to allow more elaborative processing. No gender differences were found in the implicit evaluation of sexual information, although men and women did differ at the level of self–reported sexual evaluations. Our results indicate the importance of incorporating information–processing mechanisms and emotion regulation strategies into the conceptualization of the sexual response and promote further research on the specificity, robustness, predictive validity and malleability of the cognitive–motivational processes underlying sexual arousal. Copyright © 2015 European Association of Personality Psychology